Effect of Water Absorption on Flexural Properties of Kenaf/Glass Fibres Reinforced Unsaturated Polyester Hybrid Composites Rod - Alaseel B.H.; Nainar M.A.M.; Nordin N.A.; Yahya Z.; Rahim M.N.A. (Universiti Putra Malaysia Press, 2023)
This study investigates the effect of water absorption on the flexural strength of kenaf/ glass/unsaturated polyester (UPE) hybrid composite solid round rods used for insulating material applications. Three volume fractions of kenaf/glass fibre 20:80 (KGPE20), 30:70 (KGPE30), and 40:60 (KGPE40) with three different fibre arrangement profiles of kenaf fibres were fabricated by using the pultrusion technique and were aimed at studying the effect of kenaf fibres arrangement profile and its content in hybrid composites. The fibre/ resin volume fraction was maintained constant at 60:40. The dispersion morphologies of tested specimens were observed using the scanning electron microscope (SEM). The findings were compared with pure glass fibre-reinforced UPE (control) composite. The water absorption results showed a clear indication of how it influenced the flexural strength of the hybrid and non-hybrid composites. The least affected sample was observed in the 30KGPE composite type, wherein the kenaf fibre was concentrated at the centre of a cross-section of the composite rod. The water absorption reduced the flexural strength by 7%, 40%, 24%, and 38% of glass/UPE (control), 20KGPE, 30KGPE, and 40KGPE composites, respectively. In randomly distributed composite types, the water absorption is directly proportional to the volume fraction of kenaf fibre. At the same time, flexural properties were inversely proportional to the volume fraction of kenaf fibres. Although the influence of water absorption on flexural strength is low, the flexural strength of pultruded hybrid composites was more influenced by the arrangement of kenaf fibre in each composite type than its fibre loading. Universiti Putra Malaysia Press.